Flexible and biocompatible high-performance solid-state micro-battery for implantable orthodontic system. (December 2017) - Kutbee, Arwa; Bahabry, Rabab; Alamoudi, Kholod; Ghoneim, Mohamed; Cordero, Marlon; Almuslem, Amani; Gumus, Abdurrahman; Diallo, Elhadj; Nassar, Joanna; Hussain, Aftab; Khashab, Niveen; Hussain, Muhammad
Abstract To augment the quality of our life, fully compliant personalized advanced health-care electronic system is pivotal. One of the major requirements to implement such systems is a physically flexible high-performance biocompatible energy storage (battery). However, the status-quo options do not match all of these attributes simultaneously and we also lack in an effective integration strategy to integrate them in complex architecture such as orthodontic domain in human body. Here we show, a physically complaint lithium-ion micro-battery (236 μg) with an unprecedented volumetric energy (the ratio of energy to device geometrical size) of 200 mWh/cm3 after 120 cycles of continuous operation. Our results of 90% viability test confirmed the battery's biocompatibility. We also show seamless integration of the developed battery in an optoelectronic system embedded in a three-dimensional printed smart dental brace. We foresee the resultant orthodontic system as a personalized advanced health-care application, which could serve in faster bone regeneration and enhanced enamel health-care protection and subsequently reducing the overall health-care cost. Bioelectronics: A flexible micro-battery for healthcare There is an increasing demand for advanced healthcare electronics. That can be powered by physically flexible, biocompatible and high performance energy storage devices. However, existing technologies do not allow a combination of all favorable attributes in a single system. Now Muhammad Hussain and co-workers from King Abdullah University of Science and Technology in Saudi Arabia show a physically compliant lithium ion micro-battery with an unprecedented high volumetric energy after cycling 120 times. They further integrate the battery module in a 3D printed encapsulation with near-infrared LEDs to demonstrate a smart dental brace. The present orthodontic system may be used as a personalized healthcare device that serves in faster bone regeneration and enhanced enamel healthcare protection with cost benefits.